Female land rights, crop specialization, and productivity in Paraguayan agriculture - Thomas Masterson (Levy Economics Institute of Bard College, 2007)
Previous work has shown a pattern of lower household incomes for those Paraguayan farms with female landowners in the household. The study of agricultural production reveals that Paraguayan women specialize in livestock and dairy production, while men specialize in crop production. An analysis of crop specialization and crop yields finds no significant differences in yields among households along gender lines, although women appear to specialize in food crops. Finally, households with female land rights have markedly lower rates of return on agricultural production.
Keywords: D13; Q15; O54; 330; Gender; Economic Development; Land Rights; Farm Income